Functionalized conjugated polymer/ZnO nanocomposite: Synthesis and characterization - Gupta B.; Kumar A.; Sundar V.; Prakash R. (My University, 2025)
Functionalized conjugated polymer polyanthranilic acid (PANA)/zinc oxide (ZnO) nanocomposite has been formed using co-precipitation method followed by control heating. Carboxyl functionalized polymer PANA is chemically formed in aqueous solution at acid pH and ZnO nanoparticles is formed by hydroxide precipitation at basic pH followed by control heating. A homogeneous PANA-ZnO nanocomposite is formed by co-precipitating polymer at acidic pH followed by Zn(OH)2 precipitation by increasing pH in PANA matrix and by control heating. Resulting nanocomposite is characterized under XRD, UV-vis, FT-IR, SEM and TEM techniques. Nanocomposite is heated at various temperatures (35-600°C) and characterized using XRD for observation of formation of pure ZnO phase in polymer matrix. Pronounced amorphous behavior of nanocomposite below 100°C is observed due to characteristic amorphous nature of conjugated polymer and probably complexation of Zn2+ with carboxyl functional groups (-COO-) of polymer rather than formation of pure phase of ZnO. However, above 250°C composite shows some crystalline nature. The crystallinity is explained on basis of decomposition of carboxyl functional groups of the polymer (above 250°C) therefore decomposition of polymer zinc ions complexes and formation of polymer chains with lesser number of carboxylic groups (like polyaniline) with new arrangements and formation of ZnO nanoparticles. When the sample is heated up to 600°C highly crystalline character of the composite supported almost pure ZnO phase formation with little amorphous character due to remaining polymers. Co-precipitation technique shows the formation of uniform nanocomposite and better interaction of the two components with core shell structure, which is further supported by HRTEM. © (2011) Trans Tech Publications, Switzerland.